MANAJEMEN PENANGGULANGAN KEBAKARAN DI PEKANBARU - ", Wulandari; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine Fire Management in Pekanbaru and what are the inhibiting factors. The research was motivated by firefighters due to lack of planning in facilities and infrastructure such as the number of fleets such as water catchments and posts, lack of training provided by the Fire Department to fire personnel, lack of supervision on the preparation and maintenance of firefighters, existing operational technical equipment so officers firefighters arrived at the fire site for more than 15 minutes. The concept of the theory used in this study is Prajudi Atmosudirdjo's Management Theory in M. Manullang's book which includes planning, organization, penggarahan and supervision. This study used a descriptive qualitative method. In data collection researchers used observation, interview and documentation techniques. The results of this study indicate that Fire Management in Pekanbaru has not been optimal because it is still often found that firefighters arrive late at the scene of a fire for more than 15 minutes. As for the Inhibiting Factors of Fire Management in Pekanbaru, among others, Lack of facilities and infrastructure, namely ladder cars, lack of coordination between the PLN, the Police and other agencies, and also Human Resources.Keywords: Management, Fire Prevention